Eye Diseases Classification Using Deep Learning (International Journal of Food and Nutritional Sciences, 2022)
Eyes are the most significant metaphorical sense organ. They have the potential to signify vision, knowledge, and a portal into the soul. Eyesight and vision are crucial because they allow us to connect with our environment, keep us secure, and help us preserve mental sharpness. Cataract, glaucoma, and diabetic retinopathy are the three most prevalent visual problems. Because of the increased incidence of these disorders, an early and correct diagnosis is required. The purpose of this study is to automatically identify photos containing cataracts, glaucoma, and diabetic retinopathy without the need of any intentional segmentation or feature extraction. Rather, we constructed and structured it so that patients could easily identify cataracts, glaucoma, and diabetic retinopathy. The network design is both simple and quick. The accuracy of this model has been found to be 94.55%.